2020
DOI: 10.1080/14659891.2020.1820089
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of initial service transformation in response to the COVID-19 pandemic in two inner-city substance misuse services

Abstract: Background: The COVID-19 pandemic presents challenges to substance misuse services. Patients face a higher risk of infection and transmission to others. Services were required to reconfigure quickly in response to the government lockdown. These changes had to be completed before national guidance was published. Method: To examine the strategy and operational delivery of two London boroughs and measure how convergent they were with national guidelines. Referral data were analyzed and compared to a similar time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…They concluded that patients living in rural communities also quickly adapted to changing treatment policy 28 and a further benefit to longer-interval prescribing of OAT facilitates engagement in alternative activities, including employment for the individual. This study's findings also align with a study of prescribing services in two north London Boroughs 29 and a global systematic review of 25 studies published in 2020 (mostly in the USA) on the adaptation of OAT and allied services to pandemic restrictions. 30 In this review, the most common innovation was the offer of telephone or online services, and longer interval prescribing of medication.…”
Section: Discussionsupporting
confidence: 85%
“…They concluded that patients living in rural communities also quickly adapted to changing treatment policy 28 and a further benefit to longer-interval prescribing of OAT facilitates engagement in alternative activities, including employment for the individual. This study's findings also align with a study of prescribing services in two north London Boroughs 29 and a global systematic review of 25 studies published in 2020 (mostly in the USA) on the adaptation of OAT and allied services to pandemic restrictions. 30 In this review, the most common innovation was the offer of telephone or online services, and longer interval prescribing of medication.…”
Section: Discussionsupporting
confidence: 85%
“…Multiple programs in the U.S., Canada, India, Spain, Italy and England instituted longer take-home policies for dispensed opioid agonist medications (Peavy et al [ 43 ], MacKinnon et al [ 44 ], Basu et al [ 45 ], Trujols et al [ 46 ], Vecchio et al [ 32 ] and Hazan et al [ 47 ]). This strategy was facilitated by relaxed regulations and recommendations limiting the prescription of take-home medications, especially around methadone, and a shift in emphasis by regulators on safety and access rather than preventing diversion.…”
Section: Resultsmentioning
confidence: 99%
“…A larger study on how COVID-19 related restrictions quantitatively impacted the activities of home-delivery services would be of interest to broaden our conclusions and show that those types of approaches must be developed in other countries because (i) they compliment classical HR services and (ii) they are key structures to face big-event crisis that will likely occur in the future. Nevertheless, it is important to note that remote HR structures cannot be only considered as take-home medications [ 27 , 28 ]. Indeed, first there is no need of medical prescription to access paraphernalia whereas it can be the case for some take-home medications.…”
Section: Discussionmentioning
confidence: 99%